A Review on Waste Water Treatment in Rural Areas Using Easily Accessible Plants - Sanap Santosh .T,; Dr.Ansari Ubaid .S,; Dr.Pawar Harjit .U,; Dr.Rane Harshal .S,; Kasliwal Saurabh.S,; Gore Prashant.R,; Pagare S.U, (The Bioscan, 2025)
Background- River water quality and rising water treatment costs are caused by development of land and excessive discharge from storms during the rainy seasons the natural waterfalls on the mountain are blending with the waters. Humans have conserved this water, which eventually turns into sewage and completes the hydrological cycle. Natural streams become polluted as a result of industrialization, urbanization, population development, and other causes that lower their quality, such as sewage from homes, cities, institutions, hospitals, and businesses. The ecosystem and human health are at risk from contaminated streams. As much as possible, natural materials must be used in the process of coagulation-flocculation. Objective- One of the most effective basic chemical treatments is coagulation. Techniques that could be applied to get rid of these pollutants. Natural coagulants have grown in popularity in the water and wastewater treatment industry due to their benefits over chemical coagulants Sector Microbes, plants, and animals all contain natural coagulants. The only treatment available is natural coagulants, but this is insufficient due to the increased limitations on how they work. Actually under these constrained conditions, they are being grown just as successfully as chemical coagulants thanks to technological developments and thorough research. Finding-This study examines a variety of coagulants, particularly those with a natural basis, that are employed in the process coagulation-flocculation of wastewater treatment. This review study also discusses the possibilities of naturebased materials as aids and as coagulants.